Study of the need for project-based learning citizenship e-books to expand national literacy of students pgri university palembang - Disurya, Ramanata; Danim, Sudarwan; Hamzah, Syukri; Kristiawan, Muhammad; Medriati, Rosane; Lestari, Neta Dian (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study raises the question of what resources are best suited to help students develop their civic literacy and acquire optimal knowledge about their nationality through citizenship education. The research's goal is to gather the information required for citizenship education so that students can learn as much as possible about their nationality.  This study used an exploratory survey strategy in conjunction with a quantitative research method. The sample size was 60 individuals, comprising 10 lecturers and 50 students. The inclusion criteria for students are those who have completed the Citizenship Education course so that students can provide responses based on their experience of attending lectures in nine different study programs at the Faculty of Teacher Training and Education, PGRI University Palembang. Based on research findings, 92% of teachers and students believe that the analysis of national e-book creation demands meets the Very Good standard. The findings of this research support the assumption that to increase student citizenship literacy, lecturers and students at PGRI Palembang University really need Nationality E-Books.